PROTECTION OF INDIGENOUS PEOPLES' RIGHTS TO CUSTOMARY LAND AMIDST INVESTMENT AND AREA EXPANSION - Gloria Gita Putri Ginting; Ari Prabowo (CV. Radja Publika, 2023)
This study aims to analyze the forms of legal protection for the rights of indigenous peoples to customary land amidst increasing investment and regional expansion, while simultaneously formulating strengthening measures that can maintain legal certainty and justice for indigenous peoples. The study uses a normative legal method with a statutory approach, a case approach, and a conceptual approach. Primary legal materials include the 1945 Constitution of the Republic of Indonesia, the Basic Agrarian Law, the Human Rights Law, Regulation of the Minister of Agrarian Affairs and Spatial Planning or the Head of the National Land Agency Number 14 of 2024, and Constitutional Court Decision Number 35/PUU X/2012. Data are analyzed qualitatively through systematic and teleological interpretation to examine the relationship between the recognition of customary rights, land governance, investment, and human rights protection. The results of the study indicate that customary land has a fairly strong basis for recognition in the Indonesian legal system, but its implementation still faces obstacles in the form of complicated recognition procedures, overlapping maps and permits, limited access to information, unequal bargaining positions, and consultations that do not always reflect the free and conscious consent of the community. Protection needs to be strengthened through participatory mapping, integration of customary territory data into spatial planning and licensing systems, meaningful consultation, independent legal assistance, equitable benefit-sharing agreements, and effective complaint and redress mechanisms. This approach ensures that investment can proceed without compromising the sustainability of livelihoods, cultural identity, and collective rights of indigenous communities.